Evaluación de impactos ambientales de la instalación, funcionamiento y desmantelamiento de un parque fotovoltaico en La Guajira colombiana - Guerrero-Martin, Laura Estefanía; Guerrero-Martin, Camilo Andrés; Camacho-Galindo, Leidy Stefanny (Iberoamerican Journal of Development Studies, 2024)
Renewable energies are a promising option for energy production, due to their sustainability and ability to reduce greenhouse gas emissions. Although they offer significant advantages, such as being inexhaustible resources and low climate impact, their adoption faces environmental and social challenges. The manufacture, installation, operation and decommissioning of technologies such as solar panels can generate waste and disrupt ecosystems. Therefore, it is essential to conduct comprehensive environmental assessments at all stages of renewable energy projects, considering impact variables such as impact «intensity», «extent», and «recoverability». In this article, an environmental assessment of a solar park in La Guajira (Colombia) is conducted using the methodology proposed by Vicente Conesa and an analysis is made of possible environmental management measures to minimize negative impacts, ensuring that the development of these projects is sustainable and respectful.
Keywords: assessment; environmental impacts; solar photovoltaic park; La Guajira